(3GdcGajI GdTGajI aj GdfMhs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd GHf eGdc eMeO hbO fhi EaGOI HeG ajg ELJgO GdMeO ddg GdPi ef QaOg Jhajb ef habg dMeOg hgPg CQLhRI eSJhajI Yf CcKQ GdeUfaGJ s
(3BNQgG (B:s
(3hQHeG KdK Yjf eaYdI ai eUOQ eZfjI hfaYg eTJedI hbO LYdJ fXe gPG GdHGH ecedkG CHhGH PG GdcJGH aGdMeO ddg Ydi Jcejdg ejSQkG eG Qje ef JMUjdg s
(3CQLhRI ai KdGKI BdGa HjJs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdI s
(3cJHJ YfGhjjf GdCHhGH hGdaUhd HGdMeQI s
(3MhGagG eJbUaI hde jUd GdJbUa Edi GdcdGe EdG ai GdhQbI GdCNjQIs
Keywords: (3GdfMhs